Changes in the protein profile of Quercus ilex leaves in response to drought stress and recovery. - Echevarría-Zomeño, Sira; Ariza, David; Jorge, Inmaculada; Lenz, Christof; Del Campo, Antonio; Jorrín, Jesús V; Navarro, Rafael M (Journal of plant physiology, 2009)
To characterize the molecular response of holm oak to drought stress and its capacity to recover 9-month-old Quercus ilex seedlings were subjected to three treatments for a 14-d period: (i) continuous watering to field capacity (control plants, W), (ii) no irrigation (drought treatment, D), and (iii) no irrigation for 7d followed by a watering period of 7d (recovery treatment, R). In drought plants, leaf water potential decreased from -0.72 (day 0) to -0.99MPa (day 7), and -1.50MPa (day 14). Shoot relative water content decreased from 49.3% (day 0) to 47.7% (day 7) and 40.8% (day 14). Photosystem II quantum yield decreased from 0.80 (day 0) to 0.72 (day 7) and 0.73 (day 14). Plants subjected to water withholding for 7d reached, after a 7-d rewatering period, values similar to those of continuously irrigated control plants. Changes in the leaf protein pattern in response to drought and recovery treatments were analyzed by using a proteomic approach. Twenty-three different spots were observed when comparing the two-dimensional electrophoresis profile of control to both drought and recovered plants. From these, 14 proteins were identified from tryptic peptides tandem mass spectra by using the new Paragon algorithm present in the ProteinPilot software. The proteins identified belong to the photosynthesis, carbohydrate and nitrogen metabolism, and stress-related protein functional categories.
Keywords: Drought stress; Holm oak proteome; Mass spectrometry; Quercus ilex